A note on (gDF)-spaces. (1st March 2000) - del-Vecchio, Renata R.; Pombo, Dinamérico P.; Vinagre, Cybele T. M.
Abstract : Certain locally convex spaces of scalar-valued mappings are shown to be finite-dimensional.